2012
DOI: 10.1093/jnci/djs177
|View full text |Cite
|
Sign up to set email alerts
|

A DNA Repair Pathway–Focused Score for Prediction of Outcomes in Ovarian Cancer Treated With Platinum-Based Chemotherapy

Abstract: BackgroundNew tools are needed to predict outcomes of ovarian cancer patients treated with platinum-based chemotherapy. We hypothesized that a molecular score based on expression of genes that are involved in platinum-induced DNA damage repair could provide such prognostic information.MethodsGene expression data was extracted from The Cancer Genome Atlas (TCGA) database for 151 DNA repair genes from tumors of serous ovarian cystadenocarcinoma patients (n = 511). A molecular score was generated based on the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
152
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(162 citation statements)
references
References 53 publications
4
152
2
4
Order By: Relevance
“…In contrast, several recently proposed genedriven models for predicting survival were unable to demonstrate significance for the prediction of PFS particularly in the validation set. (10)(11)(12). OS in ovarian carcinoma is influenced by various factors, such as differences in therapy after progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, several recently proposed genedriven models for predicting survival were unable to demonstrate significance for the prediction of PFS particularly in the validation set. (10)(11)(12). OS in ovarian carcinoma is influenced by various factors, such as differences in therapy after progression.…”
Section: Discussionmentioning
confidence: 99%
“…In Kang et al, a score was developed based on the expression levels of 23 genes in DNA repair pathways (11). Per patient, a point was given for each gene associated with better survival if the expression was higher than the median expression and, on the other hand, a point was given for each gene associated with poorer survival if the expression was lower than the median expression across samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that DNA repair gene polymorphisms may promote cancer progression and thus develop more aggressive tumors (Kudo et al, 2012). These DNA repair gene polymorphisms may lead to different responses to platinum-based chemotherapy by affecting the gene products' capacity to remove anthracycline -DNA adducts (Kang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many early generation ovarian cancer gene expression profiling studies focused primarily on the prognostic value of gene expression signatures. Results of these early prognostic gene expression studies [6][7][8][9][10][11][12][13][14] and those following [15][16][17][18][19][20][21][22][23][24][25] are summarized in Table 1 (Table 1). Most of these studies have identified a group of prognostically relevant genes in relatively small training sets but did, to their credit, validate the prognostic relevance of the respective gene signatures in independent cohorts.…”
Section: Gene Expression Signatures With Prognostic Relevancementioning
confidence: 99%